Electrode for sulfide-based all-solid-state battery including a conductive material having a nitrogen-containing polymer coated on the surface, and an all-solid-state battery including the same
Patent Information
- Application Number
- KR1020250025277
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2026-09-02
Smart Images

Figure PAT00005_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an electrode for a sulfide-based all-solid-state battery comprising a conductive material coated with a nitrogen-containing polymer on its surface, and an all-solid-state battery comprising the same. Background Technology
[0002] With the recent demand for improved energy density and safety in lithium-ion batteries, all-solid-state batteries utilizing solid electrolytes are attracting attention as next-generation rechargeable batteries, replacing conventional batteries that use liquid electrolytes. Solid electrolytes can be classified into polymeric organic solid electrolytes and inorganic solid electrolytes depending on the materials used; in particular, inorganic solid electrolytes offer the advantages of high cation transport coefficients and excellent ionic conductivity.
[0003] In particular, sulfide-based solid electrolytes, which are one of the inorganic solid electrolytes, are 10 -2 to 10 -4 Although they exhibit very high ionic conductivity of approximately S / cm and excellent electrochemical stability, sulfide-based solid electrolytes have poor stability in air due to high moisture reactivity upon exposure to the atmosphere, which forms H2S, and possess high interfacial resistance between electrodes because the electrolyte is a solid.
[0004] In addition, electrodes typically include a conductive material to ensure electrical conductivity within the electrode, facilitate electron transfer, and improve the electrochemical performance of the battery. However, there is an unstable interface at the contact between the conductive material and the sulfide solid electrolyte in the cathode material, and stability is reduced, such as dendrite growth, through voids caused by grain boundary defects between electrolyte particles, which leads to a significant decrease in the battery's lifespan characteristics or rate capability characteristics at high rates.
[0005] To address these issues, it is necessary to improve the air stability of the solid electrolyte, reduce interfacial resistance between the electrode and the electrolyte as well as structural defects, and simultaneously minimize defects within the electrolyte. In particular, a strategy is required to resolve chemical side reactions between the conductive material and the sulfide-based solid electrolyte.
[0006] Therefore, there is an urgent need for research on all-solid-state batteries that can develop conductive materials capable of providing high ionic conductivity and excellent material dispersibility while ensuring interfacial stability between the electrode and the electrolyte, thereby suppressing electrochemical side reactions and improving the energy efficiency and output characteristics of the battery. The problem to be solved
[0007] To solve the aforementioned problems, the present invention aims to provide an electrode for a sulfide-based all-solid-state battery comprising a conductive material that has high ionic conductivity, excellent dispersibility within the active material layer, and minimized side reactions with a sulfide solid electrolyte.
[0008] In addition, another objective of the present invention is to provide an all-solid-state battery comprising the electrode, wherein chemical side reactions between the conductive material and the sulfide solid electrolyte are effectively suppressed, thereby improving Coulomb efficiency or high-rate characteristics. means of solving the problem
[0009] In order to achieve the above-mentioned objectives, the inventors continuously researched to manufacture a cathode containing a conductive material in which chemical side reactions between the conductive material and the sulfide solid electrolyte are effectively suppressed. As a result, they discovered that when a nitrogen-containing polymer is coated on the surface of a conductive material having a specific range of diameter and length, side reactions with the sulfide solid electrolyte are minimized, thereby enabling the manufacture of an all-solid-state battery with excellent ion conductivity and improved Coulomb efficiency or high-rate characteristics, thus completing the present invention.
[0010] The present invention can provide an electrode for a sulfide-based all-solid-state battery comprising an active material layer comprising a conductive material coated with a nitrogen-containing polymer on its surface.
[0011] According to one embodiment of the present invention, the nitrogen-containing polymer may include one or more selected from the group consisting of polydopamine (PDA), polyacrylonitrile (PAN), polypyrrole (PPy), and polyaniline (PANI).
[0012] According to one embodiment of the present invention, the nitrogen-containing polymer may include a self-polymerized polydopamine polymer.
[0013] According to one embodiment of the present invention, the nitrogen-containing polymer may be bonded to the surface of the conductive material by π-π interactions.
[0014] According to one embodiment of the present invention, the nitrogen-containing polymer may be coated with a thickness of 1 to 20 nm.
[0015] According to one embodiment of the present invention, the weight ratio of the nitrogen-containing polymer to the conductive material may satisfy 0.1 to 5:1.
[0016] According to one embodiment of the present invention, the conductive material may include a rod-shaped carbon-based conductive material.
[0017] According to one embodiment of the present invention, the conductive material may have a BET specific surface area of 30 m² / g or less.
[0018] According to one embodiment of the present invention, the conductive material has a bandgap energy (E) measured by a UV-vis-NIR spectrometer. g ) can be 3.0 eV or higher.
[0019] According to one embodiment of the present invention, the conductive material may have an average diameter of 500 nm or less and an average length of 100 μm or less.
[0020] According to one embodiment of the present invention, the conductive material may comprise any one or more combinations selected from the group consisting of vapor-grown carbon fiber (VGCF) and activated carbon nanofiber (ACNF).
[0021] According to one embodiment of the present invention, the conductive material may be included in an amount of 0.1 to 20 weight percent with respect to the total weight of the active material layer.
[0022] According to one embodiment of the present invention, the active material layer may further include a positive active material, a sulfide-based electrolyte, or a mixture thereof.
[0023] According to one embodiment of the present invention, the thickness may be 10 to 500 μm.
[0024] The present invention can provide an all-solid-state battery comprising an anode layer including the electrode described above; and a sulfide-based electrolyte layer.
[0025] According to one embodiment of the present invention, the thickness ratio of the anode layer to the sulfide-based electrolyte layer may satisfy 0.05 to 1:1.
[0026] According to one embodiment of the present invention, the sulfide-based electrolyte layer is Li a PN b S c X d (Here, N is B, Al, Ga, In, Si, Ge, Sn, Pb, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W or a combination thereof, X is F, Cl, Br, I or a combination thereof, and 0≤a≤6, 0≤b≤6, 0≤c≤6, 0≤d≤6.) may include a sulfide-based electrolyte represented by
[0027] The present invention can provide a method for manufacturing an electrode for a sulfide-based all-solid-state battery, comprising the step of self-polymerizing a dopamine-based monomer and a conductive material by introducing them into a solvent containing a Tris buffer solution, a pH adjuster, and an alcohol, wherein the self-polymerization is performed by a chain oxidation reaction under conditions of pH 7 or higher.
[0028] According to one embodiment of the present invention, the alcohol may include a C1-7 alcohol.
[0029] According to one embodiment of the present invention, the pH adjuster may be a strong acid.
[0030] The present invention can provide a conductive material for a sulfide-based all-solid-state battery, wherein the conductive material has a surface coated with polydopamine, and the conductive material has an average diameter of 500 nm or less and an average length of 100 μm or less. Effects of the invention
[0031] An electrode for a sulfide-based all-solid-state battery according to one embodiment of the present invention has high ionic conductivity and excellent dispersibility within the active material layer, and minimizes side reactions with the sulfide solid electrolyte, so that even when an all-solid-state battery is formed together with the sulfide solid electrolyte, the ionic conductivity is excellent and Coulomb efficiency or high rate characteristics can be significantly improved. Brief explanation of the drawing
[0032] Figure 1 is an SEM image of a vapor-grown carbon fiber coated with a self-polymerized polydopamine polymer according to one manufacturing example and an EDS image showing the nitrogen concentration. Figure 2 is a TEM image of a vapor-grown carbon fiber coated with a self-polymerized polydopamine polymer according to the preparation example. Figure 3 is the charge and discharge voltage profile of an all-solid-state battery according to Example 5, Comparative Example 4, and Comparative Example 5. FIG. 4(a) is a graph showing the results of analyzing the lifespan characteristics (change in capacity according to the number of cycles) of all-solid-state batteries according to Example 6, Comparative Example 4, and Comparative Example 5 over 100 cycles, and FIG. 4(b) is a graph showing the results of analyzing the rate capability characteristics (change in capacity according to the number of charge / discharge cycles by current density) over multiple cycles at various current densities of 0.05 C, 0.1 C, 0.5 C, and 1.0 C. Specific details for implementing the invention
[0033] Unless otherwise defined in this specification, all technical and scientific terms have the same meaning as generally understood by those skilled in the art to which the present invention pertains. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.
[0034] The singular form used in this specification is intended to include the plural form unless specifically indicated otherwise in the context.
[0035] Additionally, numerical ranges used herein include lower and upper limits and all values within the range, increments logically derived from the form and width of the defined range, all of which are limited values, and all possible combinations of upper and lower limits of numerical ranges defined in different forms. Unless otherwise specifically defined in this specification, values outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical range.
[0036] The term “comprising” in this specification is an open description having an equivalent meaning to expressions such as “comprising,” “containing,” “having,” or “characterizing,” and does not exclude elements, materials, or processes not additionally listed.
[0037] In addition, when it is said in the present invention that a layer is located "on" another layer, this includes not only cases where a layer is in contact with another layer, but also cases where one or more other layers exist between the two layers.
[0038] Hereinafter, an electrode for a sulfide-based all-solid-state battery according to one embodiment of the present invention will be described in more detail.
[0039] The present invention provides an electrode for a sulfide-based all-solid-state battery comprising an active material layer including a conductive material coated with a nitrogen-containing polymer on its surface. The electrode for the sulfide-based all-solid-state battery may include an active material layer on a current collector, and the active material layer may include a conductive material coated with a nitrogen-containing polymer on its surface and an active material. Alternatively, the active material layer may further include a positive active material, a sulfide-based electrolyte, or a mixture thereof. The shape of the electrode may be used without limitation as long as it is a structure or a conventional configuration known in the field of electrochemistry, with respect to the remaining components excluding the conductive material.
[0040] The above current collector can be used without significant limitations as long as it is a conventional positive current collector used in the relevant technical field, and non-limiting examples may include foils made of aluminum, nickel, or a combination thereof, and the thickness of the positive current collector is not particularly limited but may be 3 to 500 μm.
[0041] According to one embodiment of the present invention, the conductive material has a nitrogen-containing polymer coated on at least one surface, and the coating form may vary depending on the shape of the conductive material. In particular, the nitrogen-containing polymer may be bonded to the surface of the conductive material by π-π interactions, and in this case, the non-covalent bonding occurs through the interaction of non-covalent electron clouds (π electrons) between aromatic rings, thereby inducing intermolecular alignment to improve interfacial stability and electrochemical performance, and thus can achieve significantly superior performance compared to a composition that is simply mixed.
[0042] According to one embodiment of the present invention, the nitrogen-containing polymer may include one or more selected from the group consisting of polydopamine (PDA), polyacrylonitrile (PAN), polypyrrole (PPy), and polyaniline (PANI). The nitrogen-containing polymer may include a polydopamine polymer in consideration of ion conductivity and ease of surface formation.
[0043] According to one embodiment of the present invention, the nitrogen-containing polymer may include a self-polymerized polydopamine polymer. In this case, by forming a uniform coating layer by forming strong π-π interactions and covalent bonds, the interfacial stability between the conductive material and the sulfide-based electrolyte is improved and side reactions with the electrolyte are suppressed, thereby improving the electrochemical performance of the battery.
[0044] According to one embodiment of the present invention, the nitrogen-containing polymer may be coated with a thickness of 0.1 to 50 nm, 1 to 20 nm, 3 to 15 nm, or 5 to 13 nm. In this case, the interfacial stability between the conductive material and the sulfide-based electrolyte can be improved, and side reactions with the electrolyte can be suppressed, thereby improving the electrochemical performance of the battery.
[0045] According to one embodiment of the present invention, the nitrogen-containing polymer may be included in an amount of 0.1 to 20 weight%, 0.1 to 10 weight%, or 0.2 to 5 weight% based on the total weight of the active material layer.
[0046] According to one embodiment of the present invention, the weight ratio of the nitrogen-containing polymer to the conductive material may satisfy 0.1 to 10:1, 0.1 to 5:1, 0.5 to 4:1, or 1 to 3:1. In this case, the weight ratio of the nitrogen-containing polymer to the conductive material may be proportional to the weight ratio of the conductive material and the monomer of the nitrogen-containing polymer introduced when the nitrogen-containing polymer is coated on the surface of the conductive material, and may be expressed as a corresponding numerical value.
[0047] According to one embodiment of the present invention, the conductive material may be a carbon body and may include carbon-based conductive materials such as particle-type, rod-type, fiber-type, or plate-type. The conductive material may include a rod-type carbon-based conductive material, and the rod-type carbon-based conductive material refers to a carbon-based conductive material having a rod-like structure.
[0048] According to one embodiment of the present invention, the conductive material may be rod-shaped, and may have an average diameter of 500 nm or less, 10 to 500 nm, 50 to 300 nm, 100 to 250 nm, or 120 to 200 nm, and an average length of 100 μm or less, 50 μm or less, 0.1 to 100 μm, 0.1 to 50 μm, 1 to 30 μm, 1 to 10 μm, or 2 to 15 μm. When the above ranges are satisfied, the dispersibility and conductivity are excellent, thereby improving the interfacial stability between the conductive material and the sulfide-based electrolyte and suppressing side reactions with the electrolyte, which can improve the electrochemical performance of the battery.
[0049] According to one embodiment of the present invention, the conductive material may have a BET specific surface area of 50 m² / g or less, 30 m² / g or less, 2 to 50 m² / g, 5 to 30 m² / g, 7 to 25 m² / g, or 10 to 20 m² / g. The specific surface area is determined by a conventional or known measurement method. When the above range is satisfied, dispersibility and conductivity can be satisfied simultaneously, side reactions with the electrolyte can be suppressed, and interfacial stability can be improved, thereby increasing the long-term lifespan and performance retention rate of the battery.
[0050] According to one embodiment of the present invention, the conductive material may have a lower bandgap energy compared to the conductive material prior to coating with a nitrogen-containing polymer. Specifically, the conductive material has a bandgap energy (E) measured by a UV-vis-NIR spectrometer. g The value may be 3.0 eV or higher, 3.0 to 10.0 eV, 4.0 to 10.0 eV, or 5.0 to 8.0 eV. An electrode containing a conductive material satisfying the above range can suppress adverse reactions with the electrolyte and improve interface stability, thereby increasing the long-term lifespan and performance retention rate of the battery.
[0051] According to one embodiment of the present invention, the conductive material may include one or more combinations selected from the group consisting of graphite, activated carbon, carbon black, carbon nanotubes (CNT), carbon nanofibers (CNF), vapor-grown carbon fibers (VGCF), and activating carbon nanofibers (ACNF). Specifically, the conductive material may include one or more combinations selected from the group consisting of vapor-grown carbon fibers (VGCF) and activating carbon nanofibers (ACNF).
[0052] According to one embodiment of the present invention, the conductive material may be included in an amount of 0.1 to 20 weight%, 0.2 to 15 weight%, 0.5 to 10 weight%, or 0.5 to 5 weight% based on the total weight of the active material layer. If the above range is satisfied, superior conductivity and interfacial stability can be achieved.
[0053] According to one embodiment of the present invention, the active material may be any conventional cathode active material used in the art without limitation, provided that it is a material capable of reversible insertion and extraction of lithium ions. Non-limiting examples include lithium cobalt oxide (LiCoO2), spinel crystalline lithium manganese oxide (LiMn2O4), lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2), lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), lithium pyrophosphate (Li2FeP2O7), lithium niobate oxide (LiNbO2), lithium iron oxide (LiFeO2), lithium magnesium oxide (LiMgO2), lithium copper oxide (LiCuO2), and lithium zinc oxide (LiZnO2). Lithium molybdate complex oxide (LiMoO2), lithium tantalum complex oxide (LiTaO2), lithium tungstate complex oxide (LiWO2), perlithium permanganate nickel cobalt complex oxide (xLi2MnO3(1-x)LiMn1-y-zNiyCozO2), lithium nickel cobalt aluminum complex oxide (LiNi 0.8 Co 0.15 Al 0.05 O2), lithium nickel cobalt manganese complex oxide (LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.4 Co 0.2 Mn 0.4 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.7 Co 0.15 Mn 0.15 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2), nickel manganese oxide (LiNi 0.5 Mn 1.5Examples include O4), but are not limited to these.
[0054] According to one embodiment of the present invention, the active material may be included in an amount of 1 to 99 weight%, 30 to 95 weight%, 50 to 95 weight%, or 70 to 90 weight% based on the total weight of the active material layer. If the above range is satisfied, superior conductivity and battery characteristics can be achieved.
[0055] According to one embodiment of the present invention, the sulfide-based electrolyte is a sulfide-based solid electrolyte described below, e.g., Li a PN b S c X d You can use it without restriction.
[0056] According to one embodiment of the present invention, the sulfide-based electrolyte may be included in an amount of 0.1 to 50 weight%, 1 to 40 weight%, 5 to 30 weight%, or 10 to 20 weight% based on the total weight of the active material layer. If the above range is satisfied, superior conductivity and battery characteristics can be achieved.
[0057] According to one embodiment of the present invention, the conductive material may be included in an amount of 0.01 to 20 parts by weight, 0.01 to 20 parts by weight, 0.01 to 20 parts by weight, or 0.01 to 20 parts by weight per 100 parts by weight of active material.
[0058] According to one embodiment of the present invention, the sulfide-based electrolyte may be included in an amount of 1 to 50 parts by weight, 5 to 30 parts by weight, or 10 to 20 parts by weight per 100 parts by weight of active material.
[0059] According to one embodiment of the present invention, the electrode may have a thickness of 5 to 1000 μm, 10 to 500 μm, or 50 to 300 μm.
[0061] Hereinafter, a method for manufacturing an electrode for a sulfide-based all-solid-state battery according to one embodiment will be described in more detail.
[0062] The present invention can provide a method for manufacturing an electrode for a sulfide-based all-solid-state battery, comprising the step of self-polymerizing a dopamine-based monomer and a conductive material by introducing them into a solvent containing a Tris buffer solution, a pH adjuster, and an alcohol, wherein the self-polymerization is performed by a chain oxidation reaction under conditions of pH 7 or higher. The polydopamine-based monomer can form π-π interactions and covalent bonds on the surface of the conductive material by a chain oxidation reaction under alkaline conditions of pH 7 or higher, thereby forming a uniform polydopamine polymer coating layer.
[0063] According to one embodiment of the present invention, the solvent may be a mixture of water and alcohol and a Trisbuffer solution, and the solvent may be adjusted using the pH adjuster to a pH of 7 or higher, 7 to 9, 7.5 to 9, or 8 to 9.
[0064] In addition, the above Trisbuffer solution comprises trisaminomethane, bis-tris(Bis(2-hydroxyethyl)aminomethane), bis-trispropane (1,3-bis(tris(hydroxymethyl)methylamino)propane), TAPSO (N-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid), TES (N-tris(hydroxymethyl)methyl-2-aminoethanesulfonic acid), TAPS (N-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid), HEPES (N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid), MOPS (3-(N-morpholino)propanesulfonic acid), PIPES (piperazine-N,N'-bis(2-ethanesulfonic acid)), and MES (2-(N-morpholino)ethanesulfonic acid). CAPS (3-(cyclohexylamino)-1-propanesulfonic acid), etc., may be used, but are not limited thereto.
[0065] According to one embodiment of the present invention, the alcohol may include a C1-10 alcohol, a C1-7 alcohol, or a C1-3 alcohol. Specifically, the alcohol may be methanol, ethanol, or propanol.
[0066] According to one embodiment of the present invention, the pH adjuster may be a strong acid, and non-limiting examples may include sulfuric acid, hydrogen chloride, hydrochloric acid, etc.
[0067] According to one embodiment of the present invention, the dopamine monomer can be used without significant limitation as long as it is a polymerizable monomer based on a catechol structure, and, for example, one or more selected from dopamine hydrochloride, dopamine, L-DOPA, 3,4-dihydroxyphenylacetic acid (DOPAC), 3-methoxycytamine, norepinephrine, epinephrine, 3,4-dihydroxyphenylethanol, 2-(4-hydroxy-3-methoxyphenyl)-ethanol, dopamine methacrylate, etc.
[0068] According to one embodiment of the present invention, the dopamine-based monomer to conductive material may satisfy a weight ratio of 0.1 to 10:1, 0.5 to 5:1, 0.8 to 3:1, or 1 to 2.5:1, and when the above range is satisfied, a stable coating layer can be formed with a thickness that exhibits dominant conductivity.
[0069] According to one embodiment of the present invention, the self-polymerization may be carried out by stirring a polymerizable composition comprising a solvent, a dopamine-based monomer, and a conductive material for at least 1 hour, at least 4 hours, at least 6 hours, or at least 10 hours. Additionally, the dopamine-based monomer may be included in an amount of 0.1 to 2 weight%, 0.2 to 1 weight%, 0.3 to 0.8 weight%, or 0.4 to 0.7 weight% with respect to the total weight of the solvent.
[0070] The present invention can provide a conductive material for a sulfide-based all-solid-state battery, wherein the conductive material has a surface coated with polydopamine, and the conductive material has an average diameter of 500 nm or less and an average length of 100 μm or less.
[0071] Specifically, the conductive material may have an average diameter of 500 nm or less, 10 to 500 nm, 50 to 300 nm, 100 to 250 nm, or 140 to 200 nm, and an average length of 100 µm or less, 50 µm or less, 0.1 to 100 µm, 0.1 to 50 µm, 1 to 30 µm, or 3 to 15 µm.
[0072] Specifically, the conductive material has a polydopamine polymer coating layer, and the coating layer may have a thickness of 0.1 to 50 nm, 1 to 20 nm, 3 to 15 nm, or 5 to 13 nm.
[0073] When the above range is satisfied, both dispersibility with the active material and ionic conductivity are excellent, and having a suitable specific surface area improves the interfacial stability between the conductive material and the sulfide-based electrolyte and suppresses side reactions with the electrolyte, thereby improving the electrochemical performance of the battery.
[0075] Hereinafter, an all-solid-state battery according to one embodiment is described, but except for including the electrode for the sulfide-based all-solid-state battery according to one embodiment, it can be manufactured into a structure known in the art using conventional manufacturing methods and materials in the art.
[0076] The present invention can provide an all-solid-state battery comprising an anode layer including the electrode described above; and a sulfide-based electrolyte layer. Since the anode layer includes the conductive material described above, interfacial stability between the electrode and the electrolyte can be secured, thereby suppressing electrochemical side reactions and enabling the manufacture of an all-solid-state battery capable of improving the energy efficiency and output characteristics of the battery.
[0077] According to one embodiment of the present invention, the thickness ratio of the anode layer to the sulfide-based electrolyte layer may satisfy 0.1 to 2:1, 0.1 to 1:1, or 0.1 to 0.5:1.
[0078] According to one embodiment of the present invention, the sulfide-based electrolyte layer may use a conventional sulfide-based solid electrolyte used in the art, and specifically, the sulfide-based electrolyte layer is Li a PN b S c X d It may include a sulfide-based electrolyte represented by (wherein N is B, Al, Ga, In, Si, Ge, Sn, Pb, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W or a combination thereof, X is F, Cl, Br, I or a combination thereof, and 0≤a≤6, 0≤b≤6, 0≤c≤6, 0≤d≤6).
[0079] Specifically, the sulfide-based solid electrolyte may include LPSCl. The sulfide-based solid electrolyte may be amorphous or crystalline, and may have an average particle size of 50 nm to 50 µm or 100 nm to 10 µm, but is not limited thereto. The sulfide-based solid electrolyte may be included in an amount of 50 wt% or more, 80 wt% or more, 90 wt% or more, 95 wt% or more, or 99 wt% or more based on the total weight of the sulfide-based electrolyte layer.
[0080] According to one embodiment of the present invention, the all-solid-state battery may further include a negative electrode layer. The all-solid-state battery may include a sulfide-based solid electrolyte layer between the positive electrode layer and the negative electrode layer. The negative electrode layer may include a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector.
[0081] Non-limiting examples of the above-mentioned negative current collector may be selected from foils made of copper, gold, nickel, or copper alloys or combinations thereof. The above-mentioned negative active material layer may be any one or more selected from the group consisting of: any one carbon selected from soft carbon, hard carbon, artificial graphite, natural graphite, expanded graphite, carbon fiber, non-blackened carbon, carbon black, carbon nanotube, acetylene black, ketjen black, graphene, fullerene, activated carbon, and mesocarbon micro beads; any one or more metals selected from silicon, tin, lithium, aluminum, silver, bismuth, indium, germanium, lead, platinum, titanium, zinc, manganese, cadmium, cerium, copper, cobalt, nickel, and iron; an alloy comprising two or more of the above-mentioned metals; and an oxide of one or more of the above-mentioned metals; and preferably, one or more selected from indium and lithium metals, but are not limited thereto.
[0082] An electrode and an all-solid-state battery according to one embodiment can be manufactured by a method commonly used in the field, for example, by means commonly used in the mixing and compression methods.
[0083] The above-mentioned all-solid-state battery can be manufactured in a shape commonly used in the field, and there are no restrictions on the external shape according to the application of the battery; for example, it can be a cylindrical shape using a can, a prismatic shape, a pouch shape, or a coin shape.
[0084] Embodiments of the present invention will be described in detail below with reference to the attached drawings. However, this is provided to enable those skilled in the art to easily implement the invention, and the present invention may be embodied in various different forms, and the concept of the present invention is not necessarily limited to these embodiments.
[0085] [Preparation Example 1]
[0086] A buffer solution was prepared by adding appropriate amounts of trisaminomethane and hydrogen chloride to a mixed solution of distilled water and methanol (9 parts distilled water to 1 part methanol (v / v)) to achieve a pH of 8.5. 160 ml of the buffer solution, 0.66 g of dopamine hydrochloride, and 0.33 g of vapor-grown carbon fiber (VGCF, average diameter: 150 nm, average length: 4 µm, BET specific surface area: 15 m² / g) were added to a reactor, and self-polymerization of dopamine monomers was induced by stirring under pH conditions of 8.5. Through self-polymerization, a polydopamine coating layer was formed on the surface of the vapor-grown carbon fiber via a chain oxidation reaction induced by alkaline pH conditions. After stirring for 20 hours, the material was centrifuged and washed at 8,000 rpm for 15 minutes, and dried in a vacuum oven at 80°C for 24 hours to finally form a polydopamine-coated surface. Vapor-grown carbon fibers were obtained. At this time, the thickness of the coating layer was measured using a high-magnification cation transmission electron microscope (TEM, JEM 1010, JEOL Ltd.) at an acceleration voltage of 120 kV, and it was confirmed that a polydopamine coating layer with a thickness of about 9 nm was formed.
[0087] SEM and EDS images (Nitrogen profile) of the manufactured polydopamine-coated vapor-grown carbon fiber (PDA@VGCF) are shown in Figures 1 (a) and (b), and TEM images are shown in Figure 2.
[0088] In addition, based on the data analyzed in the spectral region of 250–800 nm using a UV-vis-NIR spectrometer (UV-3600 Shimadzu) and the Tauc equation, the bandgap energy (E) of the polydopamine-coated vapor-grown carbon fiber (PDA@VGCF) prepared according to Preparation Example 1 and the raw vapor-grown carbon fiber (VGCF) before coating g ) was measured and the results showed that PDA@VGCF was 5.789 eV and VGCF was 2.493 eV.
[0089] [Preparation Example 2]
[0090] The above preparation was carried out in the same manner as Preparation Example 1, except that vapor-grown carbon fibers with an average length of 80 μm, which are equivalent to or similar in average diameter, were used.
[0091] [Preparation Example 3]
[0092] The procedure was carried out in the same manner as Preparation Example 1, except that carbon fibers with an average diameter of 5 μm and an average length of 1 mm (BET specific surface area: 1 m² / g) were used. In the case of Preparation Example 3, it was confirmed that the dispersibility of the carbon fibers in the solution was insufficient, and as a result, the polydopamine coating layer was formed somewhat unevenly.
[0093] [Preparation Example 4]
[0094] The above preparation was carried out in the same manner as Preparation Example 1, except that an equal amount of carbon black (super p, BET specific surface area: 62 m² / g) was added instead of vapor-grown carbon fiber.
[0096] [Example 1]
[0097] Cathode material composition (cathode active material (LiNi 0.8 Co 0.15 Al 0.05 O2 (SC-NCA, Samsung SDI) / solid electrolyte (Li6PS5Cl, LPSCl) / conductive material (polydopamine-coated vapor-grown carbon fiber of Preparation Example 1 (PDA@VGCF)) = weight ratio of 85.0 / 14.0 / 1.0) was mixed in a ball mill at 3000 rpm for 15 minutes.
[0098] The above composition was dispersed using a high-power mixer and then compressed at 1120 MPa to produce a pellet-shaped positive active material layer with a thickness of 100 μm and a diameter of 10 mm according to Example 1. At this time, the sulfur loading amount of the positive active material layer was 20 mg / cm².
[0099] [Example 2]
[0100] The above Example 1 was performed in the same manner as Example 1, except that the polydopamine-coated vapor-grown carbon fiber of Preparation Example 2, rather than Preparation Example 1, was used as the conductive material.
[0101] [Example 3]
[0102] The above Example 1 was performed in the same manner as Example 1, except that the polydopamine-coated carbon fiber of Preparation Example 3, rather than Preparation Example 1, was used as the conductive material.
[0103] [Example 4]
[0104] The above Example 1 was performed in the same manner as Example 1, except that the polydopamine-coated carbon black of Preparation Example 4 was used as the conductive material instead of Preparation Example 1.
[0105] [Comparative Example 1]
[0106] The above Example 1 was performed in the same manner as Example 1, except that no conductive material was added.
[0107] [Comparative Example 2]
[0108] The above Example 1 was performed in the same manner as Example 1, except that vapor-grown carbon fiber (VGCF) without a coating layer was used as the conductive material instead of the one prepared in Example 1.
[0109] [Comparative Example 3]
[0110] The above Example 1 was performed in the same manner as Example 1, except that as the conductive material, instead of PDA@VGCF, a composition was used in which vapor-grown carbon fiber (VGCF) without a coating layer formed in Preparation Example 1 and polydopamine were mixed in a weight ratio of 5:1. At this time, the polydopamine was prepared in the same manner as in Preparation Example 1, except that VGCF was not added.
[0112] [Examples 5 to 8 and Comparative Examples 4 to 6]
[0113] On the positive active material layer according to Examples 1 to 4 and Comparative Examples 1 to 3, a sulfide-based solid electrolyte (LPSCl 100 mg) with a thickness of 800 μm, formed by compressing at 370 MPa, was placed and compressed at 370 MPa. Subsequently, lithium (Li) metal (200 μm) and indium metal (100 μm) were sequentially stacked on a copper (Cu) foil negative current collector with a thickness of 20 μm, and a negative layer rolled at 370 MPa was placed in contact with indium (In) on the opposite side of the solid electrolyte. Finally, an aluminum (Al) foil positive current collector with a thickness of 15 μm was stacked on the positive active material layer, and these were compressed at 370 MPa to manufacture a sulfide-based all-solid-state battery (Cu-Li-In-LPSCl-positive active material layer-Al, in order).
[0115] [Evaluation Example 1] Ionic conductivity (σ Li ) and Li + Diffusion coefficient
[0116] Electrochemical Impedance Spectroscopy (EIS) analysis was performed at room temperature using Biologic SP-300. Specifically, impedance was measured by applying an AC amplitude of 10 mV in the frequency range of 3 MHz to 20 MHz, and ionic conductivity was calculated according to Equation 1 below. Ionic conductivity was calculated considering only the effect of ionic conduction, excluding the effect of electron conduction, and the results are listed in Table 1 below.
[0117] The cell for measuring ion conductivity used an electron blocking cell manufactured by laminating a 100 μm thick Li metal and a 500 μm thick sulfide-based solid electrolyte (LPSCl) formed by compressing at 370 MPa on both sides of the positive active material layer according to Examples 1 to 4 and Comparative Examples 1 to 3, and then applying pressure of 1 ton.
[0118] [Equation 1]
[0119]
[0120] (In Equation 1 above, l is the cell thickness, R is the resistance measured through EIS analysis, and S is the working area of the electrode.)
[0122] [Evaluation Example 2] Evaluation of Rate Competence and Life Characteristics
[0123] The rate capability and lifespan characteristics of the all-solid-state batteries prepared according to the above examples and comparative examples were analyzed relative to In-Li / Li using a battery analyzer (WBCS3000, Wonatech) operating in a voltage range of 1.9–3.7 V at room temperature. A torsional force of 11 N·m was applied throughout the experiment, and after undergoing two formation phases at 0.05 C, cycle tests were conducted at various current densities. Charge / discharge conditions were set at room temperature (25°C) within a voltage range of 1.9–3.7 V, and several cycle tests were performed by varying the current densities to 0.05 C (= 0.088 mA / cm²), 0.1 C, 0.5 C, and 1.0 C (= 1.6 mA / cm²). At this time, the discharge capacity at 0.05 C (DC 0.05 Discharge capacity at 1.0 C relative to ) (DC 1.0 The ratio of ) (DC 1.0 / DC 0.05 ) is shown in Table 1 below.
[0124] In addition, the charge and discharge voltage profiles of the batteries according to Example 5, Comparative Example 4, and Comparative Example 5 at a current density of 1.0 C and a voltage range of 1.9 to 3.7 V (vs. In-Li / Li) are shown in FIG. 3, and the measured initial discharge capacity, discharge capacity after 100 cycles, and initial Coulomb efficiency (initial discharge capacity / initial charge capacity) are recorded in Table 2 below.
[0125] In addition, the graph showing the results of analyzing the lifespan characteristics over 100 cycles measured at a current density of 1.0 C and a voltage range of 1.9 to 3.7 V (vs. In-Li / Li) of the batteries according to Example 5, Comparative Example 4, and Comparative Example 5 is shown in FIG. 4 (a), and the graph showing the results of analyzing the rate capability characteristics over multiple cycles at various current densities of 0.05 C, 0.1 C, 0.5 C, and 1.0 C is shown in FIG. 4 (b).
[0126] All-solid-state battery positive active material layer DC 1.0 / DC 0.05 active material layer Ionic conductivity Example 5 Example 1 5.5E-05 S / cm 0.503 Example 6 Example 2 2.0E-05 S / cm 0.402 Example 7 Example 3 1.7E-05 S / cm 0.353 Example 8 Example 4 5.9E-06 S / cm 0.154 Comparative Example 4 Comparative Example 1 1.8E-05 S / cm 0.395 Comparative Example 5 Comparative Example 2 3.8E-06 S / cm 0.153 Comparative Example 6 Comparative Example 3 3.3E-06 S / cm 0.131
[0127] As shown in Table 1 above, a battery comprising a positive electrode active material layer according to one embodiment exhibits superior ion conductivity and DC compared to the comparative example. 1.0 / DC 0.05 It was confirmed that it represents a value. In particular, Examples 5 and 6 are DC than Examples 7 and 8. 1.0 / DC 0.05 The values were expressed, confirming that rod-type conductive materials—specifically satisfying specific diameters and average lengths—compared to particle or fiber-type conductive materials, offer higher battery rate capability, meaning they can maintain high capacity even during high-speed charging and discharging.
[0128] Li + Diffusion coefficient [cm² / s] Initial discharge capacity [mAh / g] Discharge capacity after 100 cycles [mAh / g] Initial Coulomb efficiency[%] Example 5 0.40 x10 -10 209 178.5 87.6 Comparative Example 4 0.38 x10 -10 196 165.3 86.2 Comparative Example 5 0.20 x10 -10 190 118.7 85.0
[0129] As shown in Table 2, the Li+ diffusion coefficient, initial discharge capacity, discharge capacity after 100 cycles, and initial Coulomb efficiency of the electrode according to Example 5 all showed superior results compared to Comparative Example 4 without VGCF or Comparative Example 5 without a coating layer. Through this, it was confirmed that when using a conductive material coated with polydopamine, not only were side reactions between sulfide-based electrolytes suppressed, but the electrochemical performance was improved by forming an optimal ion-electron path to reduce internal resistance. Furthermore, by maintaining high initial Coulomb efficiency and excellent rate characteristics, it was confirmed that the electrode had a high capacity retention rate even in long-term cycle tests.
[0130] In addition, Nyquist plots were obtained for the electron blocking cell used in the above ion conductivity measurement through impedance analysis at high frequency (Hf), medium frequency (Mf), and low frequency (Lf), including the preparation state, after charging, and after discharging. The cell having the active material layer of Comparative Example 2 exhibited the largest Lf-semi-circle (high resistance) of 72 kΩ cm during the initial charging stage, confirming that the internal resistance was high and the conductivity was insufficient. On the other hand, the cell using Example 1 exhibited the lowest total resistance of 45 kΩ cm, and it was confirmed that the ion conductivity at the point of contact with the electrolyte (LPSCl) was improved as this low resistance was maintained throughout the discharge state.
[0131] In addition, to analyze the decomposition and interfacial reaction of the conductive material and the electrolyte (LPSCl), charging voltage profiles were obtained for electron blocking cells prepared with an active layer in which LPSCl was mixed with the PDA@VGCF of Preparation Example 1 used in Example 1 and the VGCF of Comparative Example 2, respectively, in a 7:3 ratio. The case using Comparative Example 2 showed a charging voltage of 0.35 mA g⁻¹, which is 1.8 times higher than the case using Preparation Example 1. -1 It exhibited a peak, confirming that it has a lower degradation capacity and a slower degradation rate compared to cases containing a conductive material with a polydopamine coating layer, such as the electrode according to one embodiment. Furthermore, as a result of Raman spectroscopic analysis of the electrode-electrolyte interface after charging a cell using Comparative Example 2 at 0.25 mA cm², PS4 3-It was observed that the peak shifted and the area decreased, thereby confirming that structural degradation of LPSCl was progressing. In contrast, in the case of one embodiment containing a conductive material with a polydopamine coating layer, it was confirmed that structural degradation was suppressed even after 100 cycles. Furthermore, as a result of confirming interfacial by-products through XPS analysis, it was confirmed that after 100 cycles, when Comparative Example 2 was used, LPSCl was almost completely degraded, whereas when Example 1 was used, LPSCl was structurally maintained and by-product formation was minimized.
[0132] In addition, to investigate the distribution of resistance between the conductive material and the electrolyte in the electrodes containing the active material layers of Example 1 and Comparative Example 2, the cross-sectional surface of the electrodes was analyzed using a scanning spreading resistance microscopy (SSRM, AFM NX-10, Park Systems, Co., Ltd, South Korea) equipped with a conductive diamond-coated tip (CDT-NCHR, nanosensor) with a diameter of 100 nm. At this time, the electrodes were prepared by single-grinding the electrode cross-section, and measurements were performed in a dry room using a +2.5V DC bias. The SSRM mapping image (resolution 512 pixels x 512 pixels, size 20 µm x 20 µm) showed the z-height topography and the resistance distribution of the surface.
[0133] Analysis results confirmed that the electrode of Example 1 containing PDA@VGCF maintained a lower resistance than the VGCF electrode of Comparative Example 2 and exhibited a uniform resistance distribution. Specifically, the electrode of Example 1 maintained a low value with a resistance amplitude of 1 to 10 kΩ·cm and showed a stable resistance distribution without significant changes even after 1, 50, and 100 cycles. On the other hand, the VGCF electrode of Comparative Example 2 exhibited a relatively high resistance with a resistance amplitude of 20 to 50 kΩ·cm and showed a tendency for resistance to increase as the cycles progressed. This indicates that the interfacial resistance increased and the electronic conductivity decreased as the decomposition of the electrolyte (LPSCl) proceeded more significantly in the VGCF electrode.
[0134] In addition, when comparing the average resistance values, the PDA@VGCF electrode of Example 1 (5.9 GΩ) showed a resistance approximately 36% lower than that of the VGCF electrode of Comparative Example 2 (9.2 GΩ). This was attributed to the polydopamine coating layer of the conductive material enhancing the electron conduction pathways within the electrode and suppressing interfacial reactions with the electrolyte (LPSCl). In particular, it was confirmed that the polydopamine coating layer has strong adhesive properties, which promotes the uniform distribution of the conductive material and improves network formation within the electrode, thereby enhancing electrochemical performance.
[0135] In conclusion, SSRM analysis confirmed that the PDA@VGCF electrode of one embodiment exhibited superior electronic conductivity, high interfacial stability with the electrolyte, and maintained low resistance even after long-term cycling compared to the comparative example. Through this, it was confirmed that the polydopamine coating layer of the conductive material according to one embodiment suppresses side reactions between the electrode and the electrolyte and plays a role in optimizing ion and electron conduction pathways within the battery.
[0136] In addition, the examples, experimental examples, and methods for evaluating physical properties within the specification of the present invention may be performed by referring without limitation to the non-patent document "Chemical Engineering Journal Volume 497, 1 October 2024, 154534".
[0137] As described above, the present invention has been explained by limited embodiments, but this is provided merely to aid in a more comprehensive understanding of the invention. The present invention is not limited to the above embodiments, and those skilled in the art can make various modifications and variations from this description.
[0138] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.
Claims
Claim 1 An electrode for a sulfide-based all-solid-state battery comprising an active material layer comprising a conductive material coated with a nitrogen-containing polymer on its surface. Claim 2 The electrode for a sulfide-based all-solid-state battery according to claim 1, wherein the nitrogen-containing polymer comprises one or more selected from the group consisting of polydopamine (PDA), polyacrylonitrile (PAN), polypyrrole (PPy), and polyaniline (PANI). Claim 3 In claim 1, the nitrogen-containing polymer is an electrode for a sulfide-based all-solid-state battery comprising a self-polymerized polydopamine polymer. Claim 4 An electrode for a sulfide-based all-solid-state battery according to claim 1, wherein the nitrogen-containing polymer is bonded to the surface of the conductive material by π-π interactions. Claim 5 An electrode for a sulfide-based all-solid-state battery according to claim 1, wherein the nitrogen-containing polymer is coated to a thickness of 1 to 20 nm. Claim 6 An electrode for a sulfide-based all-solid-state battery, wherein the weight ratio of the nitrogen-containing polymer to the conductive material in claim 1 satisfies 0.1 to 5:
1. Claim 7 In claim 1, the conductive material is an electrode for a sulfide-based all-solid-state battery comprising a rod-type carbon-based conductive material. Claim 8 In claim 7, the conductive material is an electrode for a sulfide-based all-solid-state battery having a BET specific surface area of 30 m² / g or less. Claim 9 In claim 7, the above conductive material has a bandgap energy (E) measured by a UV-vis-NIR spectrometer. g Electrode for a sulfide-based all-solid-state battery having a ) of 3.0 eV or higher. Claim 10 In claim 7, the conductive material is an electrode for a sulfide-based all-solid-state battery having an average diameter of 500 nm or less and an average length of 100 μm or less. Claim 11 In claim 1, the conductive material comprises one or more combinations selected from the group consisting of vapor-grown carbon fiber (VGCF) and activated carbon nanofiber (ACNF), for an electrode for a sulfide-based all-solid-state battery. Claim 12 In claim 1, the conductive material is included in an amount of 0.1 to 20 weight% based on the total weight of the active material layer, for an electrode for a sulfide-based all-solid-state battery. Claim 13 In claim 1, the active material layer further comprises a positive active material, a sulfide-based electrolyte, or a mixture thereof, for an electrode for a sulfide-based all-solid-state battery. Claim 14 In claim 1, an electrode for a sulfide-based all-solid-state battery having a thickness of 10 to 500 μm. Claim 15 An all-solid-state battery comprising: an anode layer comprising an electrode selected from any one of claims 1 to 14; and a sulfide-based electrolyte layer. Claim 16 In claim 15, an all-solid-state battery satisfying a thickness ratio of the anode layer to the sulfide-based electrolyte layer of 0.05 to 1:
1. Claim 17 In item 15, the above sulfide-based electrolyte layer is Li a PN b S c X d An all-solid-state battery comprising a sulfide-based electrolyte represented by (wherein N is B, Al, Ga, In, Si, Ge, Sn, Pb, Sb, Bi, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta, W or a combination thereof, X is F, Cl, Br, I or a combination thereof, and 0≤a≤6, 0≤b≤6, 0≤c≤6, 0≤d≤6). Claim 18 A method for manufacturing an electrode for a sulfide-based all-solid-state battery, comprising the step of self-polymerizing a dopamine-based monomer and a conductive material by introducing them into a solvent containing a Tris buffer solution, a pH adjuster, and an alcohol, wherein the self-polymerization is performed by a chain oxidation reaction under conditions of pH 7 or higher. Claim 19 In claim 18, the above alcohol is a method for manufacturing an electrode for a sulfide-based all-solid-state battery comprising a C1-7 alcohol. Claim 20 In claim 18, the above pH adjuster is a strong acid. A method for manufacturing an electrode for a sulfide-based all-solid-state battery. Claim 21 A conductive material coated with polydopamine on its surface, wherein the conductive material has an average diameter of 500 nm or less and an average length of 100 μm or less, for use as a conductive material for a sulfide-based all-solid-state battery.